Plasma concentrations of fibroblast growth factors 21 and 19 in patients with Cushing's syndrome - Ďurovcová, Viktória; Marek, Josef; Hána, Václav; Matoulek, Martin; Zikán, Vít; Haluzíková, Denisa; Kaválková, Petra; Lacinová, Zdeňka; Kršek, Michal; Haluzík, Martin (Physiological research, 2010)
The objective of this study was to measure plasma fibroblast growth factor 21 and 19 (FGF21 and FGF19) levels in patients with Cushing's syndrome (CS) and to compare it with those of lean control subjects (C) and patients with obesity (OB). Fourteen untreated patients with CS, 19 patients with OB and 36 controls were included in the study. Plasma FGF21 and FGF19 levels were measured by ELISA kits, other hormonal and biochemical parameters were measured by standard laboratory methods. Plasma FGF19 did not significantly differ among the studied groups. Plasma FGF21 levels were significantly higher in both CS and OB groups relative to C group but they did not differ between CS and OB groups. In a combined population of all three groups FGF21 levels positively correlated with BMI, waist circumference and percentage of total and truncal fat mass. Less prominent inverse relationship with these parameters was found for FGF19. Neither FGF21 nor FGF19 were significantly related to cortisol concentrations. Increased FGF21 concentrations in both patients with CS and OB relative to lean subjects suggest that excessive body fat and/or related metabolic abnormalities rather than direct effects of cortisol are responsible. In contrast neither obesity nor hypercortisolism significantly affected FGF19 concentrations.
Keywords: financování organizované; dospělí; Enzyme-Linked Immunosorbent Assay; Cushingův syndrom; fibroblastové růstové faktory; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; obvod pasu; hydrokortison; Obesity; Fibroblast Growth Factors; lidé; Hydrocortisone; Adiposity; adipozita; studie případů a kontrol; Waist Circumference; Financing, Organized; ELISA; obezita; Male; Case-Control Studies; index tělesné hmotnosti; Cushing Syndrome; lidé středního věku; mužské pohlaví; Body Mass Index; Middle Aged; Humans